Vaping and Commitment Flu-B Infection Is a Deadly Combination for Spontaneous Pneumomediastinum - Md Didar Ul Alam; Khandakar Hussain; Samsone Garedew; Muhammad imtiaz (Case Reports in Pulmonology)
Vaping or E-cigarettes were created to deliver nicotine-containing aerosol to users with a flavoring agent without agents such as tars, oxidant gases, and carbon monoxide smoke found in traditional tobacco cigarettes. The use of E-cigarettes is steadily increasing in the United States, especially among the young population. Electronic cigarettes seem capable of causing various injury patterns in the lungs, collectively called E-cigarettes or vaping-associated lung injury (EVALI). Spontaneous pneumomediastinum (SPM) is a rare finding in EVALI. Here, we report a case of spontaneous pneumomediastinum secondary to vaping in a young man with no past medical history except for daily vaping and a recent untreated influenza infection.